Evaporation of micro-droplets in cathode arc plasma coating under formed electron beam - Goncharov, A.A.; Maslov, V.I.; Litovko, I.V.; Ryabtsev, A. (Problems of Atomic Science and Technology, 2022)
Evaporation of micro-droplets in an arc plasma flow under the action of a self-consistency electron beam and the condition of direct heating of micro-droplets by fast electrons are considered. It is shown that the plasma is heated under the influence of the beam, even taking into account the fact that the electrons and ions of the plasma lose energy for the evaporation of micro-droplets. It is demonstrated that small micro-droplets evaporate more intensively. It is shown that the plasma electron density should be optimal. For the destruction of macro-particles in a plasma with a higher concentration, more powerful beams are required than in a case of plasma with a lower concentration.